The impact of entrepreneurial alertness on the performance of youth-owned enterprises in South Africa - Mahamotse, Mafadi Eliot (My University, 2020)
The South African government, in an attempt to remedy the high unemployment rate, has introduced policies and bodies to curb the unemployment rate, especially amongst the youth. This effort on the part of the government has shortcomings, as the South African GEM Report (2016/2017) depicts an alarming picture on the rate of business continuation in South Africa. The inabilities of youth to identify business opportunities, creativity and innovation are reasons stated in the GEM Report to be contributors to business discontinuation amongst youth owners. It is critical for government to develop cognitive skills amongst the youth in South Africa, since that the problem of business discontinuation is associated with cognitive capabilities. Entrepreneurial alertness is considered as an important cognitive skill that has the potential to improve enterprise performance when it is measured by scanning and search, association and connection and evaluation and judgement Data was collected from youth entrepreneurs in all provinces in South Africa, using a self-administered questionnaire and a sample size of 126 was attained. In the analysis of the data, factor analysis was utilised to reduce some variables and the variables converged into two entrepreneurial alertness dimensions, which are scanning and search and evaluation and judgement. However, scanning and search proved insignificant when regression tests were done. The findings of the study showed that entrepreneurial alertness tested with evaluation and judgement positively impacts youth-owned enterprise performance in South Africa and this impact is significant. Consequently, no evidence was found to prove that alertness tested with scanning and search has a relationship with enterprise performance. The study recommended that there is a need for an entrepreneurial alertness model that can expand alertness dimensions.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Management in Entrepreneurship and New Venture Creation to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2020
Keywords: Youth entrepreneurs; Entrepreneurial alertness; Opportunity recognition; Enterprise performance; SDG-8: Decent work and economic growth